KONTRIBUSI MAHASISWA DALAM MEMBANGUN BUDAYA ANTI KORUPSI DI LINGKUNGAN MASYARAKAT - Irzi Atarr Denanta; Muhammad Raehan Al Fazri Yasin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Corruption is a complex problem that has a negative impact on various aspects of national and public life. Building an anti-corruption culture becomes very important to address this issue. Students, as agents of change and young intellectuals, have a strategic role in this effort. This research aims to identify and analyze the contribution of students in building an anti-corruption culture within the community, including forms of concrete contributions, as well as the obstacles faced and efforts to overcome them. The research method used is a qualitative approach with data collection through in-depth interviews, participatory observation, and documentation studies. The research results show that students contribute through community education, social campaigns, and social oversight. Forms of tangible contributions include anti-corruption socialization, organizational/community activities, and utilization of social media. The obstacles faced include lack of public awareness, limited support, and environmental factors. Efforts to overcome these obstacles include increasing education, collaboration with relevant institutions, and innovation in student programs. It is concluded that the active role of students is very important in fostering an anti-corruption culture in society.